Pengaruh Perputaran Kas, Perputaran Piutang Terhadap Profitabilitas di KPN Setia Budhi - Ni Made Rianita; Dewa Ayu Putu Widyaningsih (Sekolah Tinggi Ilmu Ekonomi Satya Dharma, 2022)
The research objectives to be achieved by the authors of this study were to determine whether cash turnover hads an positive effect on profitability, whether accounts receivable turnover had an positive effect on profitability, and whether cash turnover and accounts receivable turnover together positive affect profitability at KPN Setia Budhi. This type of research data was quantitative data and sourced from secondary data in the form of the financial statements of KPN Setia Budhi. The data collection technique used in this research was documentation technique. The data analysis techniques used were multiple linear regression analysis, partial hypothesis testing (t test), simultaneous hypothesis testing (F test), and coefficient of determination test (R2). Based on the results of the research and discussion, it can be concluded that (1) cash turnover had a positive effect on profitability at KPN Setia Budhi, (2) accounts receivable turnover had a positive effect on profitability at KPN Setia Budhi, (3) cash turnover and receivables turnover together had an effect positive on profitability at KPN Setia Budhi.